Rancang Bangun Sistem Informasi Penilaian Kinerja Karyawan Menggunakan Metode Scrum Pada PT. XY - R Wahyudi Darmawan; Ferdina Kusuma; Yogi Sugiana; Dicky Zaenurdin (Universitas Tangerang Raya, 2021)
The presence of information technology such as the internet, makes it easy for humans to do work. Many ways or systems from a job that is still done in a conventional way (manual) are converted into a computerized system so that the work is more effective and efficient. One of them is the utilization of this technological development, namely the employee performance appraisal system at PT. XY. The research method used is Prototyping, which is a method for software development with stages, namely gathering requirements, building prototypes, evaluating, coding systems, testing and evaluating systems, and finally implementing systems. Using this method makes it easier to research if in the middle of the system research there is a change, so it doesn't change everything just changes based on the system flow. The purpose of this study is to build an employee performance appraisal system, which is expected to help facilitate officers in conducting employee performance appraisals. The expected result of this research is to help facilitate the HR side in assessing the performance of employees in large numbers using a computerized system so as to minimize existing deficiencies.